Synthesis and characterization of Ce(III) decorated Duolite resin and its removal performance of toxic anions from aqueous solutions - Hyder Ali Thagira Banu (KeAi Communications Co., Ltd., 2021)
Nitrate and phosphate are major threats for water/ wastewater which grounds eutrophication's and methemoglobinemia diseases, respectively and also severely hazards the safety of aquatic beings and public health's. To deal with the purging of aqueous nitrate and phosphate contamination, a low-cost Ce(III) decorated Duolite A 368 Plus resins (Ce-DA) were used. The influence of various adsorption factors was studied, such as adsorbent dosage, shaking time, pH, initial concentrations of nitrate and phosphate ions, competitive co-ions, isotherms and kinetic studies at different experimental temperatures etc. Ce-DA resin formed complexation with target nitrate and phosphate ions by adsorption via ion exchange and electrostatic attractions. Results from nitrate and phosphate adsorption showed that Ce-DA was greatly pH adjustable with an optimum pH of 3 to 7. The kinetic study revealed the pseudo-second-order and the Langmuir isotherm assessed a maximum adsorption efficiency of 138.67 and 156.26 mg/g for nitrate and phosphate ions respectively, which was higher than unloaded DA resin. The adsorption-desorption operations, demonstrating a great recovering performance of the adsorbent upto five successive cycles. This work highlights the cost-effective method to prepare promising adsorbent for efficient removal of toxic ions nitrate and phosphate from water.